Еmotional Resilience of Young People in Today’s Conditions - Solianyk, Maryna; Pohorzhelskyi, Ihor (Educological discourse, 2025)
The article examines the problems of forming the emotional vitality of young people in today’s conditions. The purpose of the article is to analyse the phenomenon of sustainability. The task of the research: on the basis of theoretical analysis and systematization of scientific sources, to determine the essence of the concept of “emotional vitality”, to analyse the understanding and interpretation of this concept by domestic and foreign researchers. Research methods: analysis, synthesis, and generalization. The key role of emotional vitality in today’s conditions is noted; the relevance and history of studies of the phenomenon of sustainability are analyzed. It has been established that emotional resilience is the key to self-improvement of both personal and professional qualities. As a result of the rapid changes taking place in society, the value of human vitality in various spheres of life naturally increases. After all, it is the high level of vitality of the individual that becomes the guarantee of its effectiveness, preservation of physical and mental health in adverse conditions of life. The increasing attention of scientists to the specified problem is also understandable. Modern scientific works highlight the results of a very wide range of research into the phenomenon of sustainability. As a result of the research, it was established that the concept of resilience can be defined as the ability to optimally resist the individual in relation to internal and external pressure. It was determined that resilience becomes difficult, gains strength precisely when a person overcomes obstacles and acquires the necessary experience. In today’s conditions, young people grow up more adapted to the surrounding reality than their parents, who often simply do not have time to adapt to the new society. In the conclusions, the main results of the research are summarized, it is stated that life resilience is considered as an adaptation mechanism of the individual, which makes it possible to model life goals, to see future prospects in the present. The novelty of the study lies in the determination of the peculiarities of the formation of the emotional resilience of Ukrainian youth in the conditions of war. The practical significance of the research results lies in the possibility of their use in the process of drawing up a program of social support for young people in the conditions of modern society. When analysing the phenomenon of emotional resilience, theoretical approaches to psychological adaptation and stress resistance were used, in particular the concepts of S. Maddi, S. Kobasa, and methodological approaches, which include analysis and synthesis of scientific literature, data generalization, and comparative analysis of approaches to resilience. These methods allow us to systematize knowledge and identify key factors that influence the development of emotional resilience in young people.